Freedom - Egmond, A. van,; Keulen, Dirk van, (Studies in Reformed Theology;, 1996)
The International Reformed Theological Institute (IRTI) was founded in 1995. Its purpose is, above all, to create a platform where Reformed theologians from all over the world can meet each other, get acquainted with each other's work, discuss theological issues and stimulate each other in scholarly theological research. Most of the articles in this volume which contains the contributions to the first conference bear upon the theme of Freedom, and often do so in a very concrete way from the perspective of the totally change political situation in the world. Next to these one finds other scholarly theological contributions. The devotional contributions to the conference have been included as well. Thus, not only does this volume provide us with reactions to the events of the last few years on the part of a number of involved theologians, but it also offers a striking perspective on the theological insights and spirituality of Reformed theologians all over the world. That is exactly the purpose of this series of Studies in Reformed Theology.